2022
DOI: 10.1021/acsptsci.2c00168
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Protein Binding of Cephalosporins

Abstract: Cephalosporins are a widely used subclass of β-lactam antibiotics that demonstrate variable protein binding independent of generation or antibiotic coverage. Prior work analyzed carbon 3 (C3) and carbon 7 (C7) substituents (locations of R2 and R1 groups respectively) for protein binding interactions. This study builds upon these results with statistical analysis of additional agents of the class. Chemical structures of 23 cephalosporins were used to identify the presence of 40 functional groups, and correlativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Kanis and colleagues performed statistical analysis between the structural characteristics of cephalosporins and their plasma protein bindings and reported that a net negative charge and the thiomethylenelinked aromatic nitrogen heterocyclic ring at the R2 side chain of cephalosporins are associated with increased plasma protein binding. 3 These observations are consistent with our results and can be explained by the structures that we determined. The crystal structures of the HSA in complex with ceftriaxone or cefazolin revealed that the substrate binding site at subdomain IB of HSA is a positively charged environment, making it more favorable for the binding of anionic compounds (Figure 6a).…”
Section: ■ Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kanis and colleagues performed statistical analysis between the structural characteristics of cephalosporins and their plasma protein bindings and reported that a net negative charge and the thiomethylenelinked aromatic nitrogen heterocyclic ring at the R2 side chain of cephalosporins are associated with increased plasma protein binding. 3 These observations are consistent with our results and can be explained by the structures that we determined. The crystal structures of the HSA in complex with ceftriaxone or cefazolin revealed that the substrate binding site at subdomain IB of HSA is a positively charged environment, making it more favorable for the binding of anionic compounds (Figure 6a).…”
Section: ■ Discussionsupporting
confidence: 93%
“…On the other hand, the R1 side chains of cephalosporins lack distinct structural features relating to plasma protein binding, and bulky or branched side chains do not appear to impact plasma protein binding (Figure 2). 3 These observations suggest that the R1 chamber is tolerant, and the cephalosporin molecules access the entrance of the R1 chamber and reach the chambers of the cephem core and R2.…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The observed increase in AUC is less likely explained by electrostatic interactions leading to greater passive reabsorption. Cephalosporins are generally known to be negatively or neutrally charged at physiologic pH [ 47 ], whereas aminoglycosides may be neutrally or positively charged [ 48 , 49 ]. However, increased AUC was observed for all antibiotics regardless of class.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the solution pH, ceftazidime exists as either neutral zwitterions (pH 2. 77 -4.26) or negatively charged species (pH > 4.26) [103]. In this work, PEI-sponges were used to extract ceftazidime through the electrostatic interaction between the negatively charged ceftazidime and the positively charged PEI.…”
Section: Effect Of Solution Phmentioning
confidence: 99%